A historical study on the growth and proliferation of community newspapers in Pangasinan - Soriano, Michelle Angelica F.; Vargas, Elisha R.; Conguico, Teresa S.; University of the Philippines. College of Mass Communication (2013)
"This study looks into the political, economic, and cultural factors that led to the growth and proliferation of community newspapers in Pangasinan. It tries to understand how and why the number of publications doubled in the previous decade despite the apparent decline in the use of traditional media. Using lenses provided by political economy and profit maximization, the research examines the factors surrounding the establishment of newspapers. It traces the history, ownership, and survival of existing publications, and identifies the motivations for putting each one up. Through interviews and content analysis, it seeks to show how politics, economics and culture affect the way community papers function in said province. As some embody the principles of journalism, several publications only exist for profit and power."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Local government and the press; Newspapers -- Objectivity; Newspaper publishing -- Philippines -- Pangasinan; Philippines -- Pangasinan -- Economic aspects; Philippine newspapers